The residual extropy of order statistics - Qiu, Guoxin; Jia, Kai (Statistics & probability letters, 2018)
Residual extropy was proposed to measure residual uncertainty of a random variable. Monotone properties and characterization results of this measure were studied. Similar properties of the proposed measure of order statistics were also discussed.